Analisis Cemaran Logam Berat Merkuri (Hg), Timbal (Pb), dan Tembaga (Cu) pada Sungai Provinsi Gorontalo - H. Hutuba, Ariani; Maku, Mohamad Aditya; Taupik, Muhammad; Adam Mustapa, Mohamad; Andy Suryadi, A. Mu'thi (State University of Gorontalo, 2025)
Heavy metals are a group of elements with high density (5 g/cm³) and unique chemical properties. They can be toxic and hazardous to the environment and human health. Heavy metal contamination in river waters is commonly caused by mercury (Hg), lead (Pb), and copper (Cu). This study aims to analyze the concentration of these metals in several rivers in Gorontalo Province using Atomic Absorption Spectrophotometry (AAS). Water samples were collected from four different rivers at a depth of 0.5 meters. The results showed that Hg concentration in the Bulango River exceeded the established quality standards, while Pb and Cu levels in the Bone River were within safe limits. The Limboto and Hulawa Rivers also met the quality standards.